Chemical profile of compounds from lichens of Bukit Larut, Peninsular Malaysia - Laily B. Din; Zuriati Zakaria; Mohd Wahid Samsudin (Universiti Kebangsaan Malaysia, 2010)
The lichen collection from Bukit Larut, Taiping, Malaysia in 1999 included Bulbothrix isidiza, Chrysothrix xanthina, Cladonia adspersa, C. verticillata, Coccocarpia palmicola, Heterodermia flabellata, H. japonica, H. obscurata, Hypotrachyna imbricatula, Leptogium azureum, Parmelinella wallichiana, Parmotrema tinctorum, P. clavuliferum, P. reticulatum, Pertusaria sp., Physma byrsaeum, Usnea baileyi and Usnea rubrotincta. Secondary metabolites could not be detected in three lichens, Coccocarpia palmicola, Leptogium azureum and Physma byrsaeum by HPLC and TLC analysis. The other 15 lichen species showed the presence of ten classes of compounds, depsides (10 compounds), depsidones (16), quinones (5), xanthones (2), naphthopyrones (1), pulvinic acid derivatives (1), diphenylethers (1), dibenzofurans (1), aliphatic acids (4) and terpenoids (3).